DIDACTIC FOUNDATIONS FOR ENHANCING PHYSICS STUDENTS’ PROFESSIONAL COMMUNICATIVE COMPETENCE IN ENGLISH WITHIN AN ESP-ORIENTED, DIFFERENTIATED, AND CONTINUOUS LEARNING FRAMEWORK - Xolmatova Maxbubaxon Axmadjon qizi (American Journals Publishing, 2026)
This article examines the didactic and methodological foundations of improving physics students’ professional communicative competence in English based on the principles of differentiation, continuity, and career orientation. In the context of globalization and the internationalization of science and technology, future physicists are required to actively participate in international research projects, academic mobility programs, and professional communication in English. The study substantiates the theoretical essence of professional communicative competence of physics students, reveals the pedagogical potential of differentiated and continuous instruction, and determines the effectiveness of career-oriented English teaching focused on physics-related academic and professional discourse.
Keywords: Physics students, professional communicative competence, English for Specific Purposes (ESP), differentiation, continuity, career orientation, higher education.